Influence of Water-Binder Ratio on the Mechanical Strength and Microstructure of Arch Shell Interface Transition Zone - Tao He; Weiheng Xiang; Jian Zhang; Cheng Hu; Gaozhan Zhang; Bin Kou (Buildings, 2022)
To prepare lightweight ultra high performance concretes used in the large-span and super-tall structure engineering fields, the effects of water-binder ratio on the mechanical performances, hydration products, and microstructure of the arched shell interface transition zone between the prewetting spherical lightweight aggregates and cement matrix were studied. The experimental results showed that adding prewetting spherical lightweight aggregates promoted the formation of an arched shell interface transition zone. And the hydration degree, microhardness, and elastic modulus values of the arched shell interface transition zone were still higher than the cement matrix. With the reduction of the water-binder ratio, the microhardness, elastic modulus, thickness, and compactness of the interface transition zone had an increase, and the internal curing action of the prewetting spherical lightweight aggregates was more obvious. Especially when the water-binder ratio was 0.18, the hydration degree of the arch shell interface transition zone increased by 18.27% compared with the cement matrix after 28 days curing time. It was concluded that the prewetting spherical lightweight aggregates could have better internal curing and arched shell effects in cement-based materials with a low water-binder ratio. Therefore, adding prewetting spherical lightweight aggregates was regarded as a potential measure to fabricate the lightweight ultra high performance concretes.